FACTOR OF SAFETY AND PROBABILITY OF FAILURE ASSESSMENT OF ROCK SLOPES IN ARTISANAL KAOLIN MINE USING LIMIT EQUILIBRIUM METHOD AND MONTE CARLO SIMULATION - Mohammad Suriyaidulman Rianse (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to evaluate the stability of three rock slopes in an artisanal kaolin mine in Semin, Gunungkidul, Yogyakarta, Indonesia, using deterministic and probabilistic approaches, and to identify the geotechnical parameters most influencing slope stability. The evaluation is conducted in compliance with Indonesian Mining Regulation (Kepmen ESDM No. 1827 K/30/MEM/2018) to provide quantitative geotechnical evidence for a mine that has been operated without prior formal geotechnical assessment. Field data were collected using the scanline method to characterize rock mass discontinuities. Laboratory tests comprising direct shear and physical properties tests were conducted to determine cohesion (c), friction angle (ϕ), and unit weight (γ) for each slope. Seismic coefficient (ks = 0,0913) was incorporated as a dynamic loading parameter. Slope stability was analyzed using the General Limit Equilibrium (GLE) method to obtain the deterministic Factor of Safety (FoS). Monte Carlo simulation (N = 10.000 iterations) was applied to determine the Probability of Failure (PoF), coefficient of variation of FoS (CoV), and reliability index (β). Sensitivity analysis was performed to quantify the contribution of each geotechnical parameter to FoS reduction. Results show that FoS values ranged from 2,019 (Slope III) to 10,55 (Slope II), all exceeding the regulatory minimum of 1,1. The PoF was 0,00% for all three slopes, well below the maximum allowable limit of 25%, with reliability indices ranging from 5,70 to 31,38. The CoV of FoS ranged from 3% to 9%, indicating low dispersion in stability outcomes despite parameter variability. Sensitivity analysis identified cohesion as the most dominant parameter in Slopes I and II, contributing 28% and 31% to FoS reduction respectively, while Slope III exhibited near-equal contributions from cohesion (20%) and friction angle (21%), reflecting its lower shear strength conditions. All three slopes satisfy the acceptance criteria of Kepmen ESDM No. 1827 K/30/MEM/2018 under current geotechnical and geometric conditions. The combined deterministic-probabilistic approach provides a more comprehensive slope safety assessment than deterministic analysis alone and is recommended for application in artisanal kaolin mining operations. Cohesion is identified as the critical parameter to be monitored and preserved to maintain slope stability.